The accuracy of ischemic core perfusion thresholds varies according to time to recanalization in stroke patients treated with mechanical thrombectomy: A comprehensive whole-brain computed tomography perfusion study. Issue 5 (May 2020) - Laredo, Carlos; Renú, Arturo; Tudela, Raúl; Lopez-Rueda, Antonio; Urra, Xabier; Llull, Laura; Macías, Napoleón G; Rudilosso, Salvatore; Obach, Víctor; Amaro, Sergio; Chamorro, Ángel
Computed tomography perfusion (CTP) allows the estimation of pretreatment ischemic core after acute ischemic stroke. However, CTP-derived ischemic core may overestimate final infarct volume. We aimed to evaluate the accuracy of CTP-derived ischemic core for the prediction of final infarct volume according to time from stroke onset to recanalization in 104 patients achieving complete recanalization after mechanical thrombectomy who had a pretreatment CTP and a 24-h follow-up MRI-DWI. A range of CTP thresholds was explored in perfusion maps at constant increments for ischemic core calculation. Time to recanalization modified significantly the association between ischemic core and DWI lesion in a non-linear fashion ( p -interaction = 0.018). Patients with recanalization before 4.5 h had significantly lower intraclass correlation coefficient (ICC) values between CTP-predicted ischemic core and DWI lesion ( n  = 54; best threshold relative cerebral blood flow (rCBF) < 25%, ICC = 0.673, 95% CI = 0.495–0.797) than those with later recanalization ( n  = 50; best threshold rCBF < 30%, ICC = 0.887, 95% CI = 0.811–0.935, p  = 0.013), as well as poorer spatial lesion agreement. The significance of the associations between CTP-derived ischemic core and clinical outcome at 90 days was lost in patients recanalized before 4.5 h. CTP-derived ischemic core must be interpreted with caution given its dependency on time to recanalization, primarily in patients with higher chances of early recanalization.